Lithospermum erythrorhizon and Forsythia suspensa Prevent Collagen Degradation and Maintain Skin Hydration by Regulating MMPs and HAS2/HYAL1 Signaling - Xiangji Jin; Qiwen Zheng; Trang Thi Minh Nguyen; Se-Jig Park; Gyeong-Seon Yi; Su-Jin Yang; Tae-Hoo Yi (Molecules)
The growing demand for aesthetic enhancement has driven the development of anti-aging cosmetics, with natural compound-based formulations emerging as a new trend to enhance efficacy. This study aims to develop a 30% ethanol extract of a 1:1 mixture of Lithospermum erythrorhizon and Forsythia suspensa (LF) as a potential material for combating UVB-induced skin aging. The bioactive components of LF extract were identified via HPLC. Antioxidant efficacy (DPPH, ABTS, and SOD) and the inhibitory effects on ROS production in cells were evaluated using flow cytometry. MMPs’ expressions were analyzed via RT-PCR, while TGF-β/Smad, ERK/AP-1, and HAS2/HYAL1 pathways were examined via ELISA and Western blot. Research findings indicate that LF effectively scavenges reactive oxygen species and enhances the activation of TGF-β signaling, promoting the synthesis of PIP (Procollagen Type I C-Peptide). Collagen degradation was mitigated through the inhibition of the AP-1 pathway, which regulates the expression of MMPs, and by suppressing the expression of TIMP. Additionally, modulation of the HAS2/HYAL1 signaling axis ensures a balanced regulation of hyaluronic acid (HA) synthesis and degradation, thereby contributing to the maintenance of collagen integrity and skin hydration. In conclusion, LF has exhibited significant protective effects against demonstrated anti-aging properties, highlighting its potential as a novel therapeutic agent in cosmetic formulations targeting aging.